Penerapan Model Pembelajaran Discovery Learning dalam Meningkatkan Kemampuan Analisis dan Hasil Belajar Fisika Siswa SMP: The Application of the Discovery Learning Model to Enhance the Analytical Skills and Physics Learning Outcomes of Junior High School Students - Naryani, Ani (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aimed to analyze the implementation of the Discovery Learning model in enhancing the analytical skills and physics learning outcomes of junior high school students. The nature of physics education, which demands higher-order thinking skills, requires a more exploratory and student-centered learning approach. This quasi-experimental research, utilizing a pretest-posttest control group design, involved 64 eighth-grade students divided into an experimental and a control group. Research instruments included an analytical skills test, a physics learning outcomes test, an observation sheet, and a student response questionnaire. Data were analyzed using t-tests, MANOVA, and correlation analysis. The results indicated that the application of Discovery Learning significantly improved students' analytical skills, with an N-Gain score of 0.74 (high category), compared to conventional learning, which yielded an N-Gain score of 0.42 (medium category). Physics learning outcomes also showed a significant increase, with an N-Gain of 0.68 in the experimental group versus 0.39 in the control group. A strong positive correlation (r=0.76) was found between analytical skills and physics learning outcomes. In conclusion, Discovery Learning is proven to be effective in developing analytical thinking skills and improving the conceptual understanding of physics among junior high school students.